Hochmittelalterliche Verse über die altersgerechte Rasur des Bartes - Haye, Thomas (Classica et Mediaevalia, 2026)
The manuscript Paris, Bibliothèque nationale de France, lat. 16289 (late 12th century) contains a previously unknown Latin poem on the age-appropriate shaving of beards. The anonymous author mocks monks who wear unkempt or untrimmed beards. The poem, which is influenced by Horace’s Ars poetica and Alain of Lille’s Parabolae, is likely to have been composed in Cistercian circles, possibly in Burgundy.